Runaway Hollywood: Cold Mountain, Romania - Lukinbeal, Chris (ERDKUNDE, 2006)
Anthony Minghella's recent movie, Cold Mountain, was an adaptation of CHARLES FRASIER's bestselling novel. The plot: A wounded confederate soldier leaves his hospital bed in Raleigh, North Carolina and makes a treacherous journey home to Cold Mountain. The book's narrative is so thoroughly embedded in the sense of place and regional culture of North Carolina and Appalachia that it is impossible to separate place and narrative. It therefore came as quite a shock to many that the filming of Cold Mountain took place primarily in Romania. In this essay I examine how just such a thing can happen; how Cold Mountain, North Carolina becomes Cold Mountain, Romania. Hollywood is now in its third wave of runaway production, or the outsourcing of feature film and television production to foreign countries. I scrutinize each of these three waves of runaway production as they relate to two key issues: economics and geographic realism. Where economics relates to keeping the cost of a production down, geographic realism plays a role in determining the suitability of a location for a narrative. All locational decisions relating to film production deal with geographic realism and economics. In the end, economics trumped geographic realism and Cold Mountain's locational choices were determined by Miramax's attitude that a A Tree is a Tree.